Nuclear Matrix Elements for β and ββ Decays and Quenching of the Weak Coupling gA in QRPA - Ejiri, Hiroyasu (Frontiers in Physics, 2019)
Recent experimental studies at RCNP on single and double beta NMEs relevant to DBDs are briefly reviewed. The axial-vector single beta NMEs are shown to be uniformly reduced by the renormalization (quenching) factor 0.5-0.6 with respect to the QRPA model NMEs due to non-nucleonic and nuclear medium effects, which are not explicitly included in the model. Impact of the reduction of the axial-vector NMEs on the DBD NMEs and DBD experiments is discussed.